Penerapan Model Pembelajaran Modelling The Way Untuk Meningkatkan Keaktifan Siswa Kelas V SD Negeri 1001 Batang Bulu - Sutan Botung Hasibuan; Era Mutiah; Ali Sadikin Harahap (Simpati, 2023)
This research aims to determine the application of the modeling the way learning model to increase student activity in Islamic Religious Education subjects regarding ablution and prayer in class V of SD Negeri 1001 Batang Bulu. The research used is classroom action research (PTK). Based on the research results, it can be concluded that: (1) Student activity before implementing the modeling the way learning model is still low. This can be seen from the results of observations that have been made. If we look at the level of activity, there are 5 students or 19% who have activity in the "Good" category and there are 21 students or 81% who have activity in the "Not Good" category. (2) Student activity after implementing the modeling the way model began to increase. In cycle I, if we look at the level of activity, there were 12 students or 46% who were active in the "Good" category and there were 14 students or 54% who were active in the "Not Good" category. In cycle II, if seen from the level of activity, there were 2 students or 8% who had activity in the "Very Good" category, there were 20 students or 77% who had activity in the "Good" category and there were 4 students or 15% who had activity in the "Good" category. "Not good.